Pengaruh Rasio Profitabilitas, Likuiditas dan Leverage Terhadap Financial Distress Pada Perusahaan BUMN yang Terdaftar di BEI Tahun 2019-2023 - Anggraini Eka Cipta; Syaiful, Syaiful (Universitas Muhammadiyah Gresik, 2025)
This research aims to examine the effect of profitability, liquidity and leverage ratios on financial distress. The dependent variable in this research is financial distress which is measured using the Springate S-score. The independent variables in this research are profitability, liquidity and leverage. The population in this study consists of state-owned companies listed on the IDX. Samples were taken for 2019-2023 and collected using the purposive sampling method. The total sample for this research is 9 companies. The test was carried out using logistic regression using SPSS 27 software. The results of the analysis showed that the profitability variable had a negative and significant influence on financial distress. The liquidity and leverage variables have a positive and significant influence on financial distress